A high molecular weight polymethyloctylsiloxane and high performance VOC film material and preparation method

High molecular weight polymethyloctylsiloxane homopolymer was prepared by cationic ring-opening polymerization, which solved the problems of low octyl content and insufficient solvent resistance in the existing film, and achieved the preparation of high-performance VOCs films.

CN119735811APending Publication Date: 2025-04-01DALIAN EUROFILM IND
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411909789.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing polyoctylmethylsiloxanes used for VOCs separation are block copolymers, with low octyl content, resulting in insufficient solvent resistance of the film and affecting the life of the film.

Method used

High molecular weight polymethyloctylsiloxane homopolymer was prepared by cationic ring-opening polymerization to improve the octyl content, enhance the separation performance and solvent resistance of the film.

Benefits of technology

It improves the separation performance and solvent resistance of the gas separation membrane, and extends the service life of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735811A_ABST
    Figure CN119735811A_ABST
Patent Text Reader

Abstract

The present application discloses a high molecular weight polymethyloctylsiloxane and a high performance VOC membrane material and a preparation method. The high molecular weight polymethyloctylsiloxane is prepared by ring-opening polymerization of raw materials containing cyclosiloxane, a catalyst, and an end-capping agent. The high performance VOC membrane material is a high molecular weight polysiloxane homopolymer, which is prepared by ring-opening polymerization of cyclosiloxane monomers, and contains double bond functional groups at both ends. The high performance VOC membrane material provided by the present invention is dip-coated on a porous base membrane to prepare a gas separation composite membrane for VOC treatment, which can improve the membrane separation performance, and at the same time, the solvent resistance of the gas separation performance of the VOC membrane material is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high molecular weight polymethyloctylsiloxane and a high performance VOC membrane material and a preparation method, belonging to the field of membrane separation technology. Background Art

[0002] Organic vapor (VOC) mainly comes from the exhaust gas of the petrochemical industry, organic matter in the chlorine-containing system used for washing, and organic solvents in the coating system. These VOCs discharged into the atmosphere will cause a series of problems such as health, environment, and safety. The methods for treating VOC mainly include combustion, catalytic oxidation, condensation, absorption, adsorption, and membrane separation. Membrane technology has the advantages of small investment, high separation efficiency, low energy consumption, simple operation, and no secondary pollution, and has been widely used in the treatment of VOC.

[0003] The separation membrane is the core of the membrane recovery system. The performance of the membrane determines the applicability of the membrane technology. High separation selectivity can give the membrane recovery system a higher recovery efficiency. The separation layer of the composite membrane used to treat VOC is mostly silicone rubber. Among them, PDMS silicone rubber membrane is widely used.

[0004] POMS silicone rubber replaces part of the methyl groups in PDMS silicone rubber with octyl groups to obtain higher membrane separation selectivity. According to the principle of like dissolves like, a high octyl content means that the solvent resistance of the membrane material decreases. POMS silicone rubbers available on the market or reported in the literature are all block copolymers, in which the proportion of octylsiloxane repeating units is relatively low, generally between 10-60%. Further increasing the octyl content will reduce the solvent resistance, which directly affects the life of the membrane. Therefore, it is necessary to find a polysiloxane raw material with a high octyl content and good solvent resistance to produce high-performance VOCs membranes. Summary of the invention

[0005] According to a first aspect of the present application, a high molecular weight polymethyloctylsiloxane is provided, wherein the high molecular weight polymethyloctylsiloxane is prepared by ring-opening polymerization of raw materials containing cyclosiloxane, a catalyst, and a capping agent.

[0006] Optionally, the cyclosiloxane is selected from at least one of cyclotetramethyltetraoctylcyclotetrasiloxane and trimethyltrioctylcyclotrisiloxane.

[0007] Optionally, the catalyst is selected from at least one of trifluoromethanesulfonic acid, fluorine-containing carboxylic acid and sulfuric acid.

[0008] Optionally, the end-capping agent is selected from at least one of tetramethyl divinyl disiloxane, dimethyl divinyl dichloro disiloxane, and trichlorovinyl siloxane.

[0009] Optionally, the amount of the catalyst used is 0.05wt%~0.1wt% of the cyclosiloxane.

[0010] Optionally, the amount of the catalyst used is any value selected from 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt% or a range between any two of the above values ​​when the cyclosiloxane is independently selected.

[0011] Optionally, the amount of the end-capping agent is 0.001 wt.% to 0.005 wt.% of the cyclosiloxane.

[0012] Optionally, the amount of the end-capping agent used is any value selected from 0.001 wt.%, 0.002 wt.%, 0.003 wt.%, 0.004 wt.%, 0.005 wt.% or a range between any two of the above values ​​when the cyclosiloxane is independently selected.

[0013] According to the second aspect of the present application, a method for preparing the high molecular weight polymethyloctylsiloxane described above is provided, the preparation method comprising: The mixture containing cyclosiloxane and catalyst is subjected to reaction I, and a capping agent is added to react II to obtain the high molecular weight polymethyloctylsiloxane.

[0014] Optionally, the temperature of the reaction I is 50-80° C., and the time of the reaction I is 1-3 h.

[0015] Optionally, the temperature of the reaction I is independently selected from any value of 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or a range between any two of the above values.

[0016] Optionally, the reaction time I is independently selected from any value among 1 h, 2.5 h, 2 h, 2.5 h, 3 h, or a range between any two of the above values.

[0017] Optionally, the reaction II includes a first reaction stage and a second reaction stage; The temperature of the first reaction stage is 60-80°C, and the time of the first reaction stage is 1-3h; The temperature of the second reaction stage is 40-50° C., and the time of the second reaction stage is 1-2 hours.

[0018] According to a third aspect of the present application, a method for preparing a high-performance VOC film material is provided, the preparation method comprising the following steps: Step S1: stirring a mixture containing high molecular weight polymethyloctylsiloxane, a crosslinking agent, a catalyst, and a solvent to obtain a separation layer solution; Step S2: coating the separation layer membrane liquid on the base membrane, drying it, and then performing a heat cross-linking treatment to obtain the high-performance VOC membrane material; The high molecular weight polymethyl octyl siloxane is selected from the high molecular weight polymethyl octyl siloxane described above.

[0019] Optionally, in step S1, the cross-linking agent is selected from at least one of polymethyl hydrogen siloxane, polyethyl hydrogen siloxane, and polymethyl hydrogen-polydimethyl siloxane.

[0020] Optionally, the catalyst is selected from at least one of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex, cis-dichlorobis(diethyl sulfide)platinum(II), and chloroplatinic acid.

[0021] Optionally, the solvent is selected from at least one of isooctane, n-hexane and n-heptane.

[0022] Optionally, the bottom membrane is a porous ultrafiltration bottom membrane, and the pore size of the porous ultrafiltration bottom membrane is 10~2000nm.

[0023] Optionally, the base membrane is a porous ultrafiltration base membrane, and the pore size of the porous ultrafiltration base membrane is independently selected from any value of 10nm, 50nm, 100nm, 500nm, 1000nm, 1500nm, 2000nm or a range between any two of the above.

[0024] Optionally, the base film includes at least one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, and polyetherimide.

[0025] Optionally, in step S1, the amounts of the components in the separation layer solution are as follows, calculated by weight: 30-100 parts of high molecular weight polymethyl octyl siloxane; Cross-linking agent 0.1~0.3 parts; Catalyst 0.05~0.2 parts; 900~970 parts of solvent.

[0026] Optionally, in step S1, the stirring temperature is 40-80° C., and the stirring time is 1-3 h.

[0027] Optionally, in step S2, the temperature of the thermal cross-linking treatment is 100-120° C., and the time of the thermal cross-linking treatment is 20-40 min.

[0028] According to a fourth aspect of the present application, a high-performance VOC film material prepared by the preparation method described above is provided.

[0029] As an optional implementation method, the present application is implemented through the following technical solutions: The specific preparation process is as follows: (1) Preparation of separation layer membrane material: Add a catalyst to the cyclosiloxane, heat and stir, add a capping agent to the system after a period of reaction, continue stirring for a certain period of time, lower the reaction temperature and continue stirring to obtain high molecular weight polymethyloctylsiloxane.

[0030] (2) Preparation of composite membrane: Add the prepared high molecular weight polymethyloctylsiloxane, crosslinking agent and catalyst into isooctane and stir evenly to prepare separation layer membrane liquid. Coat the separation layer membrane liquid on the porous ultrafiltration bottom membrane, dry it, and then perform heat crosslinking treatment to prepare the gas separation membrane.

[0031] The beneficial effects of this application include: The high molecular weight polymethyloctylsiloxane provided in the present application is prepared into a high molecular weight polysiloxane homopolymer by adopting a cationic ring-opening polymerization method, thereby improving the membrane separation performance and ensuring the solvent resistance of the gas separation membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 FIG. 4 is a diagram of a test device for a gas separation membrane in an embodiment of the present application.

[0033] In the figure: 1. Nitrogen cylinder; 2. Oxygen cylinder; 3. Pressure reducing valve; 4. Pressure gauge; 5. Membrane evaluation tank; 6. Stop valve; 7. Soap bubble flow meter. DETAILED DESCRIPTION

[0034] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0035] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0036] The molecular weight of the siloxane homopolymer prepared in the embodiment of the present invention is characterized by the viscosity of its solution, which is tested by a viscometer. The test solution is a 30% isooctane solution of polymethyloctylsiloxane. The test temperature is 30° C. and the viscometer speed is set to 50 rpm.

[0037] The permeation and separation performance of the composite membrane prepared in the embodiment of the present invention is measured by the permeation rate J of pure O2 and N2 and the O2 / N2 separation coefficient α O2 / N2 To characterize.

[0038] The detection method in the embodiments of the present application is as follows: like Figure 1As shown, place the cut circular membrane into the membrane evaluation pool 5 and seal it tightly. Open the N2 gas cylinder 1 to pass N2, and at the same time open the stop valve 6 to purge the membrane feed side with N2. After 2 minutes, close the stop valve 6 and adjust the pressure reducing valve 3 so that the pressure gauge 4 shows 0.2 MPa. After the system is stable for 1 hour, use a stopwatch to test the time it takes for the soap bubble flowmeter 7 connected to the membrane permeation side to pass 5 ml and record it. Open the O2 gas cylinder 2 and test the O2 permeation and separation performance of the composite membrane. The test method is the same as that of N2.

[0039] O2 and N2 permeation rates J Calculated by the following formula:

[0040] Where: V—the flux of permeate gas under test conditions, cm 3 ; t—test time, s; A—effective membrane area, cm 2 ; Δp—transmembrane pressure difference, cmHg; T0, p0—temperature and pressure under test conditions, K, cmHg; Separation coefficient α between O2 and N2 (O2 / N2) are the permeation rates of the two gases J O2 and J N2 Ratio of: Example 1

[0041] Add 2000 parts of cyclotetramethyl tetraoctylsiloxane to a three-necked raw silk flask equipped with a spherical condenser and a thermometer, introduce nitrogen, drop 1 part of trifluoromethanesulfonic acid, stir and heat to 60°C, react for 1 hour, add 0.1 parts of tetramethyl divinyl disiloxane, continue to react at 60°C for 1 hour, then lower the temperature to 40°C, react for 2 hours, and stop the reaction. Add an equal amount of isooctane to the three-necked flask to dissolve the product, wash with deionized water to remove the catalyst, and remove the solvent and oligomers by vacuum distillation to obtain the product, octyl polymethylsiloxane homopolymer, the viscosity of its 30% isooctane solution is 25000cp.

[0042] 30 parts of octyl-containing polymethylsiloxane homopolymer were dissolved in 970 parts of isooctane, 0.1 parts of polymethylhydrogensiloxane and 0.1 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 40°C for 60 min to prepare a separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polysulfone porous ultrafiltration bottom membrane, dried at room temperature for 10 min, and dried at 100°C for 20 min to prepare a composite membrane. The permeability and separation performance of the composite membrane for O2 and N2 fluxes were tested at 25°C, and the results were as follows: N2 =0.15m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Soak in isooctane solvent for 5 days, take out and dry to test its performance, J N2 =0.16m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Example 2

[0043] Add 2000 parts of cyclotetramethyl tetraoctylsiloxane to a three-necked flask equipped with a spherical condenser and a thermometer, pass nitrogen, drop 1.5 parts of trifluoromethylsulfonic acid, stir and heat to 80°C, react for 1 hour, add 0.2 parts of tetramethyl divinyl disiloxane, continue to react at 80°C for 1 hour, then lower the temperature to 40°C, react for 2 hours, and stop the reaction. Add an equal amount of isooctane to the three-necked flask to dissolve the product, wash with deionized water to remove the catalyst, and remove the solvent and oligomers by vacuum distillation to obtain the product, octyl polymethylsiloxane homopolymer. The viscosity of its 30% isooctane solution is 20000cp.

[0044] 50 parts of octyl-containing polymethylsiloxane homopolymer were dissolved in 950 parts of isooctane, 0.1 parts of polymethylhydrogensiloxane and 0.1 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 40°C for 60 min to prepare a separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polyetherimide porous ultrafiltration bottom membrane, dried at room temperature for 10 min, and dried at 100°C for 20 min to prepare a composite membrane. The permeation and separation performance of the composite membrane for O2 and N2 fluxes tested at 25°C were J N2 =0.25m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Soak in isooctane solvent for 5 days, take out and dry to test its performance, J N2 =0.27m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Example 3

[0045] Add 2000 parts of trimethyl trioctyl cyclotrisiloxane to a three-necked raw silk flask equipped with a spherical condenser and a thermometer, pass nitrogen, drop 1.5 parts of trifluoromethylsulfonic acid, stir and heat to 50°C, react for 3 hours, add 0.2 parts of dimethyl divinyl dichlorodisiloxane, continue to react at 60°C for 3 hours, then lower the temperature to 50°C, react for 1 hour, and stop the reaction. Add an equal amount of isooctane to the three-necked flask to dissolve the product, wash with deionized water to remove the catalyst, and remove the solvent and oligomers by reduced pressure distillation to obtain the product, octyl polymethylsiloxane homopolymer. The viscosity of its 30% isooctane solution is 18000cp.

[0046] 100 parts of octyl-containing polymethylsiloxane homopolymer were dissolved in 900 parts of n-hexane, 0.3 parts of polymethylhydrogen-polydimethylsiloxane and 0.05 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 40°C for 3 hours to prepare a separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polyetherimide porous ultrafiltration bottom membrane, dried at room temperature for 10 minutes, and dried at 120°C for 20 minutes to prepare a composite membrane. The permeability and separation performance of the composite membrane for O2 and N2 fluxes tested at 25°C were J N2 =0.20m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Soak in isooctane solvent for 5 days, take out and dry to test its performance, J N2 =0.35m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Example 4

[0047] Add 2000 parts of trimethyl trioctyl cyclotrisiloxane to a three-necked raw silk flask equipped with a spherical condenser and a thermometer, pass nitrogen, add 1.5 parts of sulfuric acid, stir and heat to 80°C, react for 1 hour, add 0.2 parts of trichlorovinyl siloxane, continue to react at 80°C for 1 hour, then lower the temperature to 40°C, react for 2 hours, and stop the reaction. Add an equal amount of isooctane to the three-necked flask to dissolve the product, wash with deionized water to remove the catalyst, and remove the solvent and oligomers by vacuum distillation to obtain the product, octyl polymethylsiloxane homopolymer. The viscosity of its 30% isooctane solution is 18500cp.

[0048] 30 parts of octyl-containing polymethylsiloxane homopolymer were dissolved in 970 parts of n-hexadecane, 0.1 parts of polyethylhydrogensiloxane and 0.2 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 80°C for 1 hour to prepare a separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polyacrylonitrile porous ultrafiltration bottom membrane, dried at room temperature for 10 minutes, and dried at 100°C for 40 minutes to prepare a composite membrane. The permeability and separation performance of the composite membrane for O2 and N2 fluxes tested at 25°C were J N2 =0.25m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Soak in isooctane solvent for 5 days, take out and dry to test its performance, J N2 =0.30m 3 / m 2 ·h·bar, α (O2 / N2) =3.0. Comparative Example 1

[0049] 30 parts of vinyl methylsiloxane-octyl methylsiloxane-dimethylsiloxane copolymer were dissolved in 970 parts of isooctane, 0.1 parts of polymethyl hydrogen siloxane and 0.1 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 40°C for 60 min to prepare the separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polysulfone porous ultrafiltration bottom membrane, dried at room temperature for 10 min, and dried at 100°C for 20 min to prepare a composite membrane. The permeability and separation performance of the composite membrane for O2 and N2 fluxes were tested at 25°C, and the results were J N2 =0.25m 3 / m 2 ·h·bar, α (O2 / N2) =2.35. Soaked in isooctane solvent for 5 days, taken out and dried to test its performance, J N2 =0.36m 3 / m 2 ·h·bar, α (O2 / N2) =2.05. Comparative Example 2

[0050] 50 parts of vinyl methylsiloxane-octyl methylsiloxane-dimethylsiloxane copolymer were dissolved in 950 parts of isooctane, 0.1 parts of polymethyl hydrogen siloxane and 0.1 parts of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and stirred at 40°C for 60 min to prepare the separation layer membrane liquid. The separation layer membrane liquid was evenly coated on the polyetherimide porous ultrafiltration bottom membrane, dried at room temperature for 10 min, and dried at 100°C for 20 min to prepare a composite membrane. The permeability and separation performance of the composite membrane for O2 and N2 fluxes were tested at 25°C, and the results were J N2=0.2m 3 / m 2 ·h·bar, α (O2 / N2) =2.33. Soaked in isooctane solvent for 5 days, taken out and dried to test its performance, J N2 =0.3m 3 / m 2 ·h·bar, α (O2 / N2) =2.0.

[0051] Comparing Example 1 with Comparative Example 1, the N2 flux and O2 / N2 selectivity of the composite membrane prepared in Example 1 are J N2 =0.15m 3 / m 2 ·h·bar, α O2 / N2 =3.0. The selectivity of the composite membrane is higher than that of the block copolymer POMS composite membrane (α O2 / N2 =2.35). The selectivity of the composite membrane remained unchanged after being immersed in isooctane solvent.

[0052] Comparing Example 2 with Comparative Example 2, in Example 2, the content of the catalyst was increased, the molecular weight of the obtained siloxane homopolymer was increased, and the N2 flux and O2 / N2 selectivity of the prepared composite membrane were J and J, respectively. N2 =0.25m 3 / m 2 ·h·bar, α O2 / N2 =3.0. The selectivity of the composite membrane remained unchanged after being immersed in isooctane solvent.

[0053] Since the existing polyoctylmethylsiloxanes used for VOCs separation are all block copolymers with low octyl content, the solvent resistance of the membrane is acceptable. According to the characteristics that long-chain alkyl substitution is more conducive to cationic ring-opening polymerization, the present invention controls the synthesis reaction temperature and other conditions to prepare a high molecular weight polymethyloctylsiloxane homopolymer with high octyl content, which can improve the separation performance of the prepared gas separation membrane. At the same time, the high molecular weight polymethyloctylsiloxane has a higher entanglement density, and its network structure is more compact after further cross-linking, and the solvent resistance of the membrane is improved.

[0054] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A high molecular weight polymethyloctylsiloxane, characterized in that: The high molecular weight polymethyloctylsiloxane is prepared by ring-opening polymerization of raw materials containing cyclosiloxane, a catalyst and a capping agent.

2. The high molecular weight polymethyloctylsiloxane according to claim 1, characterized in that The cyclosiloxane is selected from at least one of cyclotetramethyltetraoctylcyclotetrasiloxane and trimethyltrioctylcyclotrisiloxane; Preferably, the catalyst is selected from at least one of trifluoromethanesulfonic acid, fluorinated carboxylic acid, and sulfuric acid; Preferably, the end-capping agent is selected from at least one of tetramethyl divinyl disiloxane, dimethyl divinyl dichloro disiloxane, and trichlorovinyl siloxane; Preferably, the amount of the catalyst is 0.05wt.%~0.1wt.% of the cyclosiloxane; Preferably, the amount of the end-capping agent is 0.001 wt.% to 0.005 wt.% of the cyclosiloxane.

3. The method for preparing the high molecular weight polymethyloctylsiloxane according to any one of claims 1 to 2, characterized in that: The preparation method comprises: The mixture containing cyclosiloxane and catalyst is subjected to reaction I, and a capping agent is added to react II to obtain the high molecular weight polymethyloctylsiloxane.

4. The preparation method according to claim 3, characterized in that: The temperature of the reaction I is 50-80° C., and the time of the reaction I is 1-3 hours.

5. The preparation method according to claim 3, characterized in that: The reaction II includes a first reaction stage and a second reaction stage; The temperature of the first reaction stage is 60-80°C, and the time of the first reaction stage is 1-3h; The temperature of the second reaction stage is 40-50° C., and the time of the second reaction stage is 1-2 hours.

6. A method for preparing a high-performance VOC film material, characterized in that: The preparation method comprises the following steps: Step S1: stirring a mixture containing high molecular weight polymethyloctylsiloxane, a crosslinking agent, a catalyst, and a solvent to obtain a separation layer solution; Step S2: coating the separation layer membrane liquid on the base membrane, drying it, and then performing a heat cross-linking treatment to obtain the high-performance VOC membrane material; The high molecular weight polymethyl octyl siloxane is selected from the high molecular weight polymethyl octyl siloxane according to any one of claims 1 to 2.

7. The preparation method according to claim 6, characterized in that: In the step S1, the crosslinking agent is selected from at least one of polymethyl hydrogen siloxane, polyethyl hydrogen siloxane, and polymethyl hydrogen-polydimethyl siloxane; Preferably, the catalyst is selected from at least one of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex, cis-dichlorobis(diethyl sulfide)platinum(II), and chloroplatinic acid; Preferably, the solvent is selected from at least one of isooctane, n-hexane and n-heptane; Preferably, the bottom membrane is a porous ultrafiltration bottom membrane, and the pore size of the porous ultrafiltration bottom membrane is 10-2000 nm; Preferably, the base film includes at least one of polysulfone, polyethersulfone, polyacrylonitrile, polyvinylidene fluoride, and polyetherimide.

8. The preparation method according to claim 6, characterized in that: In step S1, the amounts of the components in the separation layer solution are as follows, calculated by weight: 30-100 parts of high molecular weight polymethyl octyl siloxane; Cross-linking agent 0.1~0.3 parts; Catalyst 0.05~0.2 parts; 900~970 parts of solvent.

9. The preparation method according to claim 6, characterized in that: In step S1, the stirring temperature is 40-80°C and the stirring time is 1-3h; Preferably, in step S2, the temperature of the thermal crosslinking treatment is 100-120° C., and the time of the thermal crosslinking treatment is 20-40 min.

10. A high-performance VOC film material prepared by the preparation method according to any one of claims 6 to 9.